Penerapan Augmented Reality Pengenalan Monumen sebagai Upaya Pariwisata Berkelanjutan - Yuniarto, Dwi; Helmiawan, Muhammad Agreindra (LPPM & Fakultas Teknologi Informasi UNSAP, 2023)
The implementation of Augmented Reality (AR) in monument recognition as a sustainable tourism strategy is an innovative approach that blends cultural heritage with modern technology. This research explores the concept and implementation of AR as a tool that enables monument visitors to dynamically interact with their cultural heritage. The methodology of a prototype is employed as the framework for this study. The research begins with an in-depth analysis of the current state of tourism and the challenges faced in cultural heritage preservation. A comprehensive literature survey is conducted to understand the latest developments in AR technology and its applications in the tourism sector. The outcome of this research is the development of an AR application that can be used by monument visitors. This application allows users to view monuments in their historical context, obtain in-depth explanations of architectural and cultural elements, and participate in interactive experiences that enhance their understanding of cultural heritage. The prototype methodology guides the stages of developing this AR application, from initial design to testing and ongoing improvement. Testing of the AR application is carried out at various monument locations, involving visitors in assessing its usage and its impact on the tourism experience. Evaluation results demonstrate a significant increase in visitor satisfaction, their understanding of monuments, and their interest in participating in sustainable tours. This research underscores the significant potential of AR technology in enhancing cultural heritage preservation efforts and sustainable tourism. The prototype methodology used not only guides the development of the AR application but also ensures that the application is user-centric and provides a satisfying experience. However, challenges in implementing this technology include technical aspects, financial sustainability, as well as education and training to maximize the benefits of AR in a tourism context. In conclusion, the application of AR in monument recognition is a crucial step towards a more sustainable future for tourism, with a focus on satisfying visitor experiences.